Bullying and school failure among primary school children: A clinical perspective on emotional and cognitive impacts - Chaima, Saci; Lamia, Djenadi (The International tax journal, 2024)
School bullying is a growing concern in primary education systems worldwide, with increasing attention being paid to its long-term psychological and academic consequences. This theoretical article aims to explore the clinical relationship between school bullying and academic failure among primary school children, focusing on the emotional and cognitive dimensions of the phenomenon. Drawing on a wide range of psychological theories, including Bandura’s Social Learning Theory and Maslow’s Hierarchy of Needs, this paper analyzes how repeated exposure to bullying can lead to diminished self-esteem, emotional distress, cognitive disengagement, and, ultimately, school failure. The article also examines the profiles of both bullies and victims, highlighting the psychological mechanisms that contribute to dysfunctional behaviors and poor academic performance. Through a clinical lens, we argue that bullying is not merely a disciplinary or social issue, but a significant psychological risk factor that interferes with a child's learning process, mental health, and overall development. Based on a synthesis of recent literature and case-based clinical observations, this work emphasizes the urgent need for early psychological interventions, safe school environments, and integrated support systems.